Valoración de la dinámica demográfica reciente de los territorios de montaña del País Vasco a partir de estudio de casos - Galdós Urrutia, Rosario; Porcal Gonzalo, María Cruz; Ruiz Urrestarazu, Eugenio (Geographicalia, 2014)
Three mountainous zones in the Basque Country, namely Macizo del Gorbea, Macizo del Ernio and Montaña Alavesa, were studied with the objective of revealing the diversity contained within the Basque Mountain Area. This article centres on the geodemographic analysis of the said zones through an assessment of the recent demographic transformation process: growth and its determinant factors; population and settlement distribution; and the structural features of the population. From the study made it can be deduced that, although some common lines do exist, clear geodemographic differences can be detected between the different mountain environments, which depend on two factors: scale and measuring instruments used.